Ajaran Rasul Paulus “Menjadi Serupa dengan Kristus” Ditinjau dari Konsep “meniru” Richard Dawkins - Valeria Sonata (Jurnal Apokalupsis, 2023)
This article aims to examine the suitability of the human evolutionary process, as proposed by Richard Dawkins, with the concept of “becoming like Christ," especially through the use of the term "imitate" in the teachings of the Apostle Paul. This study identifies the problem that scientists, including those who believe in God, may experience difficulty reconciling their faith with the scientific evidence supporting evolution. Imitating Richard Dawkins' "meme" offers a new understanding of evolution that does not only derive from innate genetic material, but also from nature, character, and habits, as in the teachings of the Apostle Paul. This article uses a qualitative approach with narrative and literary research methods. This research concludes that religion, like science, has undergone an evolutionary process. Interdisciplinary efforts are needed to integrate the insights of historians, anthropologists, psychologists, economists, scholars, and others. Evolution conflicts can be reconciled with Richard Dawkins' views.